Clinical Evaluation of Metal Dental Prostheses in Captive Wild Felids - Fecchio, Roberto Silveira; Teixeira, Rodrigo Hidalgo Friciello [UNESP]; Barbosa, Bruna; Gioso, Marco Antonio (SAGE Publications, 2024)
Captive felids are prone to dental fractures, and the recommended treatment involves endodontics (root canal treatment), prosthodontics (coronal restoration), or tooth extraction. A single-unit dental prosthesis can restore the crown of a tooth whose structure has been partially or completely lost. Nine animals out of 35 captive wild felids kept under human care in 7 different Brazilian institutions were selected for the study. The animals selected included the little spotted cat (Leopardus tigrinus), ocelot (L. pardalis), margay cat (L. wiedii), pampas cat (L. colocolo), jaguarundi cat (Puma yagouaroundi), puma (P. concolor), jaguar (Panthera onca), lion (P. leo), and tiger (P. tigris). Nineteen canine prosthodontic crowns (18 full and one 3/4) were cemented using dual-cure resin cement and their feasibility was evaluated for 30 months. Fourteen (73%) remained fixed to the tooth and 5 (27%) were lost after the evaluation period. This study aimed to assess the longevity of prosthodontic crowns in the canine teeth of wild felids. Furthermore, it aimed to determine the functionality and longevity of teeth which had received prosthodontic crowns.
Keywords: cementation; dental prostheses; veterinary dentistry; wild felids; zoo medicine